2014
DOI: 10.1007/s00128-014-1308-4
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticide Levels in Breast Milk in Guerrero, Mexico

Abstract: In Mexico, organochlorine pesticides were used in public health and agriculture programs, causing chronic exposure to the population. Human breast milk samples were collected from 171 mothers who were residents from Guerrero, Mexico. Analysis was carried out by gas chromatography. Median concentrations (mg/kg on fat basis) for the following pesticides were: HCB, 0.009; β-HCH, 0.004; pp'DDE, 0.760; op'DDT, 0.016; pp'DDT, 0.045; and Σ-DDT, 0.833. These values are lower than in other States in Mexico, and in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Another study from Korea also revealed the presence of organochlorine pesticides (OCPs) chlordanes, aldrin, dichlorodiphenyltrichloroethanes (DDTs), dieldrin, heptachlors, endrins, hexachlorocyclohexanes (HCHs), hexachlorobenzene (HCB), toxaphenes and mirex, in milk (Kim et al ., 2013). Organochlorine pesticides HCB, β-HCH, pp’DDE, pp’DDT, pp’DDT, Σ-DDT were present in breast milk of the population in Guerrero, Mexico, proportionally to exposure (Chávez-Almazán et al ., 2014). …”
Section: Effect In Humansmentioning
confidence: 99%
“…Another study from Korea also revealed the presence of organochlorine pesticides (OCPs) chlordanes, aldrin, dichlorodiphenyltrichloroethanes (DDTs), dieldrin, heptachlors, endrins, hexachlorocyclohexanes (HCHs), hexachlorobenzene (HCB), toxaphenes and mirex, in milk (Kim et al ., 2013). Organochlorine pesticides HCB, β-HCH, pp’DDE, pp’DDT, pp’DDT, Σ-DDT were present in breast milk of the population in Guerrero, Mexico, proportionally to exposure (Chávez-Almazán et al ., 2014). …”
Section: Effect In Humansmentioning
confidence: 99%
“…Los plaguicidas organoclorados pueden monitorearse en poblaciones humanas a través del análisis de leche materna, lo que refleja en parte la cantidad de contaminante presente en el ambiente de donde fue absorbido por los individuos estudiados (IPCS 2011). Existen escasos estudios sobre estos contaminantes orgánicos persistentes en la población del estado de Guerrero (Chávez-Almazán et al 2014, 2016. Respecto a la distribución de estos compuestos en el estado, no hay información que permita identificar las diferencias en la exposición entre sus habitantes y de esta forma brindar un panorama de la problemática existente que coadyuve a la toma de decisiones de las instituciones públicas ambientales y sanitarias tendientes a disminuir el contacto con estos contaminantes y prevenir sus efectos adversos a largo plazo en las personas expuestas.…”
Section: Introductionunclassified